Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00264-013-1907-4
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of shoulder arthroplasty to reverse implants: clinical and radiological results using a modular system

Abstract: Purpose Revision of a shoulder arthroplasty to a reverse arthroplasty is a highly demanding procedure. The aim of this study is to report the clinical results of hemi and total shoulder prosthesis revisions to reverse implants without removal of the humeral stem, using a modular shoulder replacement system (SMR Lima LTD). We retrospectively reviewed 26 patients who underwent an operation from 2004 to 2009. Methods The patients were divided into two groups: in Group I, 18 patients underwent a revision of hemiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 43 publications
3
39
0
1
Order By: Relevance
“…This is consistent with the literature, in which the most common reasons for failure of hemiarthroplasties or total shoulder arthroplasties include superior migration or subluxation of the humeral head secondary to rotator cuff dysfunction occurring in 17% to 54% of patients [2,7,13,17,19,30,34] with the likelihood of a higher incidence with longer followup [5,34]. Our study showed that a modular stem designed for exchange has distinct advantages in the case of revision and that the quality of implantation (prosthetic height and torsion) at the index operation is important, because improper positioning can mandate stem exchange even in a system designed to allow stem preservation.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the literature, in which the most common reasons for failure of hemiarthroplasties or total shoulder arthroplasties include superior migration or subluxation of the humeral head secondary to rotator cuff dysfunction occurring in 17% to 54% of patients [2,7,13,17,19,30,34] with the likelihood of a higher incidence with longer followup [5,34]. Our study showed that a modular stem designed for exchange has distinct advantages in the case of revision and that the quality of implantation (prosthetic height and torsion) at the index operation is important, because improper positioning can mandate stem exchange even in a system designed to allow stem preservation.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study reported a 0 % rate of humeral tuberosity or shaft fractures in patients with platform humeral stems converted to RTSA [13]. A similar study of 26 patients with full modular stems likewise reported no intraoperative humeral complications [18].…”
Section: Uses and Advantages Of A Platform Systemmentioning
confidence: 92%
“…Castagna, et al recently published a series of 26 patients who underwent conversion of a previous shoulder arthroplasty to an RTSA using a platform system [18]. The index operation in 18 of the patients was hemiarthroplasty for fracture; the remaining 8 patients had an ATSA for glenohumeral arthritis.…”
Section: Clinical Outcomes Using Platform Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors chose metallic lateralisation of the COR, which keeps the humeral bearing away from the pillar of the scapula. Several implants were designed according to this concept: the RSP (DJO Surgical, Austin, TX, USA) [16], the SMR (Lima, Udine, Italy) [5][6][7] and the Arrow RSA (FH Orthopedics, Mulhouse, France) [28,42]. In the latter, the design of the glenosphere and metal baseplate allows COR lateralisation of 8.5 mm.…”
Section: Introductionmentioning
confidence: 99%